Low Autophagy (ATG) Gene Expression Is Associated with an Immature AML Blast Cell Phenotype and Can Be Restored during AML Differentiation Therapy. (18th March 2018) - Jin, Jing; Britschgi, Adrian; Schläfli, Anna M.; Humbert, Magali; Shan-Krauer, Deborah; Batliner, Jasmin; Federzoni, Elena A.; Ernst, Marion; Torbett, Bruce E.; Yousefi, Shida; Simon, Hans-Uwe; Tschan, Mario P.
Abstract : Autophagy is an intracellular degradation system that ensures a dynamic recycling of a variety of building blocks required for self-renewal, homeostasis, and cell survival under stress. We used primary acute myeloid leukemia (AML) samples and human AML cell lines to investigate the regulatory mechanisms of autophagy and its role in AML differentiation. We found a significantly lower expression of key autophagy- (ATG-) related genes in primary AML as compared to healthy granulocytes, an increased autophagic activity during all- trans retinoic acid- (ATRA-) induced neutrophil differentiation, and an impaired AML differentiation upon inhibition of ATG3, ATG4D, and ATG5. Supporting the notion of noncanonical autophagy, we found that ATRA-induced autophagy was Beclin1-independent compared to starvation- or arsenic trioxide- (ATO-) induced autophagy. Furthermore, we identified PU.1 as positive transcriptional regulator of ATG3, ATG4D, and ATG5. Low PU.1 expression in AML may account for low ATG gene expression in this disease. Low expression of the autophagy initiator ULK1 in AML can partially be attributed to high expression of the ULK1-targeting microRNA-106a. Our data clearly suggest that granulocytic AML differentiation relies on noncanonical autophagy pathways and that restoring autophagic activity might be beneficial in differentiation therapies.